A Study on Mutual Fund Investors' Awareness - Dr. M Sumathy; Akshaya S. Das (HM Journals, 2022)
Research looking into people's knowledge and comprehension of mutual funds, which are investment vehicles that pool money from multiple participants to buy a diverse portfolio of securities, can be termed a mutual fund awareness study. In order to determine people's acquaintance with mutual funds, their investment habits, and their opinions towards various types of funds, the study may comprise surveys or interviews with a representative sample of the public. The study may also look into the variables like income, education, age, and risk tolerance that affect people's decisions to invest in mutual funds.